Building a Foundation for Literacy: Strategies for Cultivating a Love of Reading in ECE (Early Childhood Education) Children - Yusdiana Yusdiana; Eka Setiawati; Ayu Fajarwati (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to identify and analyze the effectiveness of various methods of teaching reading to early childhood (ECE) through a systematic literature review. Early literacy is a crucial factor in children's cognitive, language and social development. However, choosing the right teaching method can be a complex process. This research uses the PRISMA method to collect and analyze scientific literature from various sources, with a focus on phonetic, whole language and level reading methods. The findings of this study identified that each method has its own advantages and disadvantages, and the selection of an appropriate method must take into account the child's individual characteristics and needs. The implications of this research include the importance of developing a rich literacy environment, positive interactions between parents and children, and collaboration between educators and parents in supporting early childhood literacy development.